Effect of prior strain and heating rate on the microstructures, mechanical properties and plastic anisotropy of AA5182 sheets - Xiuchuan Lei; Adrien Chapuis; Qianning Guo; Kaiyun Xiang; Xiaofang Yang; Robert E. Sanders (Journal of Materials Research and Technology)
The crystallographic texture and grain size of aluminum sheet products greatly influence their final mechanical properties. A series of AA5182-O 1 mm thick sheet samples were manufactured to create a variety of crystallographic textures and grain structures. Tensile tests were carried out in the longitudinal (0°), 45°, and transverse (90°) direction, from which r-values were computed which can be related to the recrystallized textures of the sheet samples. Good formability (resistance to thinning) is generally reflected in high uniform elongation and r-value. High levels of strain prior to annealing resulted in finer grains as expected, but a slow heating rate promoted the retention of deformation texture components whereas rapid heating and larger prior strain resulted in higher levels of random and Cube texture. The highest average r-value and Δr, reflecting planar anisotropy, were associated with a slow heating rate and a smaller prior strain. Conversely, high deformation and fast heating resulted in very low Δr (less than 0.02). The observed process effects on the textures and r-values are explained by the competition between recrystallization mechanisms. Random textures, promoted by high strain, fast heating rate, and particle-stimulated nucleation (PSN), actually resulted in a higher volume of Cube grains, compared to the retained dominating rolling textures in the slowly heated samples. These results reflect the importance of prior strain and recovery on the anisotropy of 5xxx auto sheet. As input, the textures were used in a visco-plastic self-consistent (VPSC) model, and predictions showed a reasonable correlation with the experimental r-values.